Desenvolvimento de técnicas manipulativas osteopáticas para tratamento da síndrome do impacto do ombro baseado na biomecânica - Louro, Sanny Mendes (2019)
Shoulder impingement syndrome is the most common pathology among all pathologies affecting the shoulder joint. In the treatment of this pathology, emphasize the manual therapy techniques, including osteopathy, which is a technique based on the biomechanical recovery of the musculoskeletal system. In this direction, this work uses global osteopathic manipulative techniques and presents complementary techniques, known as functional recovery techniques for the impingement syndrome treatment. The number of sessions required for complete treatment was associated with total recovery of shoulder joint motion, absence of pain and improvement of the functional disability and pain test result - SPADI, with a maximum limit of 20 sessions for the treatment of shoulder. The treatment was effective in reach full range of motion, reducing treatment time, and stopping the shoulder pain symptom, in addition to achieving great improvement in the SPADI test result for all participants.